Mr Study on Food Traceability Importance in Tourism Industry - Zrnić, Miloš (The Business of Tourism, 2020)
Depending on how we nourish ourselves on daily basis talks a lot about us at the first place. Food can be a cure and the poison at the same time. How food has been used, prepared and digest, is crucial element for daily energy level that everybody needs to flourish in today word. In order to achieve that goal, we need food that’s been checked, approved, transported to our local markets. With help from proper traceability system we can secure food safety, and prevent any critical situation from happening in the whole process of food distribution. That’s why today, more than ever, attention on tracking whole distribution process in the food chain is of huge importance globally. This paper will be focusing on study/importance of traceability system in tourism industry, requirements for food traceability and importance of traceability itself.